Tourism as a Driver of Development: A Predictive Study of Tourism Revenues in Algeria - Rabah, Dilmi (Journal of Ecohumanism, 2025)
This study aims to examine the role of tourism in Algeria’s economy and development, as well as its revenues. The theoretical part of the study addressed the conceptual framework of tourism, focusing on the main determinants of tourism growth, including GDP, security stability, the country’s environmental, cultural, and historical diversity, and tourists’ behaviors. The applied part of the study focused on forecasting tourism revenues in Algeria using the Autoregressive Integrated Moving Average (ARIMA) model, implemented through the artificial intelligence software ORANGE.The results of forecasting tourism revenues showed that these revenues remain stable throughout the forecast period for Algeria, estimated for the next 7 years. This stability is primarily attributed to the country’s heavy dependence on the hydrocarbons sector and the neglect of other sectors, including tourism, as well as the absence of a serious and clear governmental strategy to develop and diversify the tourism sector.